FINE NEEDLE ASPIRATION CYTOLOGY- EFFECTIVENESS IN CERVICAL TUBERCULOSIS DIAGNOSIS IN TERTIARY HEALTH CARE CENTRE. - Dr. Aizaz Fatima; Dr. Mohammed Imran khan; Dr. naish Akhtar; Dr Arunim Shikhar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction- Tuberculosis (TB) is a chronic granulomatous infection principally caused by Mycobacterium TB and less frequently by ingestion of Mycobacterium bovis infected unpasteurized cow’s milk or by other atypical mycobacteria. Tuberculosis is a specific infectious disease caused by bacteria belonging to the "Mycobacterium tuberculosis complex". It presents a great social and economic problem and is one of the major factors responsible for the high morbidity and mortality in India. The incidence of tuberculous cervical lymphadenopathy now accounts for two third of the extra pulmonary tuberculous lymphadenopathy. Most of these are supposed to be tuberculous in origin because of greater incidence of pulmonary tuberculosis in our country. At the same time there are other causes of lymph-adenopathy which are usually misdiagnosed as tuberculosis. It has been a common problem for both to clinicians as well as pathologist from to diagnose tuberculosis.Methos and materials- The present work is carried out in 100 clinically suspected cases of tuberculous cervical lymphadenitis attending E.N.T., Surgery, Paediatrics, pathology, and Medicine Department of central India institute as an outdoor/indoor patient during the period of one year. Patients with enlarged cervical lymph nodes with a history suggestive of tuberculosis were included after taking an informed consent.Results- Study was done on 100 clinically suspected cases of tuberculous cervical lymphadenitis, Tuberculosis was diagnosed in 57% cases by FNAC, smear and culture together, the maximum incidence of tuberculosis was observed in second and third decades, Females were more affected (64%) than males with the ratio of 1:2.3. By FNAC 42% accuracy was obtained, 30% cases were AFB smear positive in our study this rate of incidence is nearer to other authors. In our culture study, 57 cases were diagnosed as tuberculous and 4 cases as non-tuberculous cervical lymphadenitis. Culture positive was higher in granulomatous necrotic lesions. Sensitivity, specificity and predictive values of culture study were significantly higher than FNAC and smear. These methods of investigation need considerable experience and confidence of a pathologist who perform the procedure for a better result. When culture was taken as Gold Standard, cytology was found to be more sensitive than smear.Conclusions – from this study we concluded that Both FNAC and smear are quick, simple, less traumatic and cost-effective methods and used as a routine investigating procedure in OPD of urban and semi-urban hospitals. Simplicity of these techniques (FNAC & Smear) combined with early availability of results and good diagnostic accuracy warrants their clinical application. Missed cytological diagnosis and isolation of non-tuberculous mycobacteria justify culture studies on all suspected tuberculous lymphadenitis cases